The Galungan Holiday in Postmodern Historical Studies - Wijaya, I Nyoman (Diponegoro University, 2024)
This study examines the topic of Galungan, a cultural practice in Bali that occurs every 210 days. Galungan is not only celebrated in Bali but also in almost all major cities in Indonesia and around the world. In every celebration, Galungan is always referred to as the day of victory of dharma (virtue) over adharma (evil). This topic is examined using a postmodern approach, employing Foucault's theory of power-knowledge relations. The aim is to uncover the hidden power-knowledge relations within it. To achieve this goal, Galungan is positioned as subjugated knowledge. The research question is, what knowledge is subjugated, so that a single discourse emerges that Galungan is a celebration of the victory of dharma over adharma? This issue is examined using Foucault's methods of genealogy of power and archaeology of knowledge. The research results show that the reference to Galungan as the day of victory of dharma over adharma is the result of demythologization, a fictional story that is reconstructed and considered as truth. In order to realize this discourse, a great deal of old knowledge is subjugated, such as Galungan as the day of the arrival of ancestral spirits and the economic cycle of society. At the surface level, this effort is successful, in pemedek [worshippers] these two things are more prominent than highlighting the victory of dharma over adharma.